Immune stimulation during chemotherapy increases incidence of acute graft versus host disease in acute myeloid leukemia: A study on behalf of SFGM-TC and ALFA. (March 2017) - Wang, Lining; Raffoux, Emmanuel; Thomas, Xavier; Yakoub-Agha, Ibrahim; Bouhris, Jean-Henri; de Botton, Stéphane; Michallet, Mauricette; Quoc, Stéphanie Nguyen; Chantepie, Sylvain; Deconinck, Eric; Caillot, Denis; Turlure, Pascal; et al.
Highlights: Cutaneous immune stimulation during induction increases the incidence of skin aGVHD. Digestive immune stimulation during induction increases the incidence of gut aGVHD. Prolonged febrile duration correlates with elevated incidence of grade II–IV aGvHD. Identification of a group of patients with higher risk of aGvHD. Abstract: 60–70% of AML patients have an indication of allogeneic hematopoietic stem cell transplantation (allo-HSCT) during their treatment. Graft versus host disease (GvHD), the major cause of mortality and comorbidities post-transplantation, develops by immunological mechanism and decides greatly prognosis and quality of life (QoL) of graft recipient. Current GvHD prophylaxis is not personalized. Infections, toxicities and leukemic infiltration complicate the first chemotherapy phases prior to allo-HSCT. They, to certain extent, induce local immune stimulation. Impact of immune stimulation of this period on incidence of GvHD has not been evaluated. We retrospectively studied 238 AML patients transplanted at first remission from 21 French centers in the ALFA-0702 protocol and found that cutaneous and digestive immune stimulation during induction increases the incidence of skin and gut aGVHD, respectively. Furthermore, prolonged febrile duration correlates with elevated incidence of grade II–IV aGvHD. Thus, we identified a group of patients with higher risk of aGvHD. The benefit of personalized GvHD prophylaxis should be explored in a prospective cohort to decrease incidence of aGvHD in these patients and improve their QoLs.